Is LMNB1 a susceptibility gene for neural tube defects in humans?. Issue 6 (3rd June 2013) - Robinson, Alexis; Partridge, Darren; Malhas, Ashraf; De, Sandra C.P.; Gustavsson, Peter; Thompson, Dominic N.; Vaux, David J.; Copp, Andrew J.; Stanier, Philip; Bassuk, Alexander G.; Greene, Nicholas D.E.
<x xml:space="preserve">Abstract</x> BACKGROUND Lamins are intermediate filament proteins that form a major component of the nuclear lamina, a protein complex at the surface of the inner nuclear membrane. Numerous clinically diverse conditions, termed laminopathies, have been found to result from mutation of LMNA. In contrast, coding or loss of function mutations of LMNB1, encoding lamin B1, have not been identified in human disease. In mice, polymorphism in Lmnb1 has been shown to modify risk of neural tube defects (NTDs), malformations of the central nervous system that result from incomplete closure of the neural folds. METHODS Mutation analysis by DNA sequencing was performed on all exons of LMNB1 in 239 samples from patients with NTDs from the United Kingdom, Sweden, and United States. Possible functional effects of missense variants were analyzed by bioinformatics prediction and fluorescence in photobleaching. RESULTS In NTD patients, we identified two unique missense variants that were predicted to disrupt protein structure/function and represent putative contributory mutations. Fluorescence loss in photobleaching analysis showed that the A436T variant compromised stability of lamin B1 interaction within the lamina. CONCLUSION The genetic basis of human NTDs appears highly heterogenous with possible involvement of multiple predisposing genes. We hypothesize that rare variants of LMNB1 may contribute to susceptibility to NTDs. Birth Defects Research (Part A) 97:398–402, 2013. © 2013 Wiley Periodicals, Inc.